Xerocomus chrysenteron lectin: identification of a new pesticidal protein - Trigueros, Véronique; Lougarre, Andrée; Ali-Ahmed, Djamila; Rahbé, Yvan; Guillot, Jean; Chavant, Louis; Fournier, Didier; Paquereau, Laurent (Biochimica et biophysica acta, 2003)
Xerocomus chrysenteron is an edible mushroom with insecticidal properties. In an earlier work, we found that proteins are responsible for this toxicity. Here we describe the purification of a ∼15 kDa lectin, named XCL, from the mushroom. Its cDNA and gDNA were cloned by PCR strategies and a recombinant form was expressed in Escherichia coli. Sequence alignments and sugar specificity showed that this protein is the third member of a new saline-soluble lectin family present in fungi. This protein, either purified from mushroom or expressed in vitro in E. coli, was found to be toxic to some insects, such as the dipteran Drosophila melanogaster and the hemipteran, Acyrthosiphon pisum. The lectin possesses a high insecticidal activity compared to lectin isolated from leguminosae ( Lathyrus ochrus) or from the snowdrop ( Galanthus nivalis).